Perception towards buying motor insurance in Kota Kinabalu Sabah / Markderron James - James, Markderron (2013)
The primary concern of this study is to examine the consumer perception towards buying motor insurance in Kota Kinabalu, Sabah. In attempting to study this research, several interrelated questions need to be designed in order to meet with the research objectives (Bertice Berry, 2013). Basically, the factors of buying motor insurance and the perception of the consumer were used as the research questions. During the research process, there will be a single dependent variable and a set of independent variables. The dependent variable is the Consumer Perception towards buying motor insurance, while the independent variables consist of brand name and image, service and quality, existence of bancassurance and brand loyalty. A descriptive research is conducted to ascertain and will be able to described characteristic of a variable of interest in a situation. For instance the independent variables will influence the perception towards motor insurance. By referring to Uma Sekaran 2003, the goal for descriptive study research is to provide relevant aspects that comprises of individual, organization and other perspective.